2014
DOI: 10.1007/978-3-642-55375-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Ferroic and Multiferroic Domain Walls

Abstract: Ferroic materials are defined by having an order parameter that can be oriented in more than one direction. Within a ferroic material, then, there can be regions (domains) with different orientation of the order parameter: magnetic domains in ferromagnets, polar domains in ferroelectrics, twins in ferroelastics. Domain walls, or domain boundaries, are the separations between adjacent domains. In the last few years, domain walls have moved from being regarded as an inevitable by-product of the domains, to regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…While flipping along the long side of the tetragonal unit cell creates a ferroelectric-only 180°d omain wall instead, in which the a domain and c domain are formed head-to-tail with each other [15][16][17]. The domain wall is said to be continuous, which means it can only end in other domain walls or grain boundaries [18]. There are discontinuities of polarization in the perpendicular direction of domain walls, where the local displacements would be expected to accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…While flipping along the long side of the tetragonal unit cell creates a ferroelectric-only 180°d omain wall instead, in which the a domain and c domain are formed head-to-tail with each other [15][16][17]. The domain wall is said to be continuous, which means it can only end in other domain walls or grain boundaries [18]. There are discontinuities of polarization in the perpendicular direction of domain walls, where the local displacements would be expected to accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor which affects domain wall dynamics is the width of the walls, since thin walls are more likely to be pinned by point defects than thick walls. According to Catalan et al [60], domain walls which are both ferroelectric and ferroelastic are expected to be thinner than pure ferroelastic walls but thicker than purely ferroelectric walls. On the other hand, Jia et al [61] found that charged twin walls in PbZr 0.2 Ti 0.8 O 3 thin films are ∼10 times thicker than uncharged walls.…”
Section: Discussion and Conclusion: Acoustic Properties Of Domain Wal...mentioning
confidence: 99%
“…136 In-depth information on the properties and potential applications of multiferroic domain walls can be found in refs. [137][138][139] .…”
Section: Multiferroic Domain Walls and Emergent Functional Propertiesmentioning
confidence: 99%